THE URGE TO OPTIMIZE THINKING PROCESS: THE INFLUENCE OF PARENT AND PEER ATTACHMENT ON PROBLEMATIC INTERNET USE (PIU) MEDIATED BY EXECUTIVE FUNCTION: Urgensi Mengoptimalkan Proses Berpikir: Kontribusi Kelekatan kepada Orang Tua dan Teman Sebaya terhadap Problematic Internet Use (PIU) Dimediasi oleh Executive - Yuliana Mukti Rahmawati; Adiyo Roebiyanto (Faculty of Social Science and Human Ecology, IPB University, 2025)
Attachment relationships are shaped by higher-order cognitive abilities that help individuals regulate their behavior, including internet usage, which is a prevalent activity among students. The purpose of this study is to assess the mediating role of executive function (EF) in the relationship between individual attachment and problematic internet use (PIU) behavior. EF is believed to serve as a buffer against the negative effects of weak attachment between individuals and their parents or peers, thereby helping to suppress PIU behavior. This study employed a quantitative research design with 127 college students from DKI Jakarta. Convenience sampling was used to select participants. Attachment was measured using the Inventory of Parent and Peer Attachment – Revision (IPPA-R), PIU was assessed using the Indonesian Problematic Internet Use Scale (IPIUS), and EF was evaluated using the Amsterdam Executive Function Inventory (AEFI). The mediation regression analysis revealed a significant indirect effect of attachment to parents on PIU, mediated by EF. It is recommended that parents foster early interactions with their children to optimize their cognitive development and take peer influences into consideration when supporting their children’s behavior regulation.